Genome‐Wide Association Mapping of Crown Rust Resistance in Oat Elite Germplasm. Issue 2 (1st July 2017) - Klos, Kathy Esvelt; Yimer, Belayneh A.; Babiker, Ebrahiem M.; Beattie, Aaron D.; Bonman, J. Michael; Carson, Martin L.; Chong, James; Harrison, Stephen A.; Ibrahim, Amir M.H.; Kolb, Frederic L.; McCartney, Curt A.; McMullen, Michael; et al.
Abstract : Oat crown rust, caused by Puccinia coronata f. sp. avenae, is a major constraint to oat ( Avena sativa L.) production in many parts of the world. In this first comprehensive multienvironment genome‐wide association map of oat crown rust, we used 2972 single‐nucleotide polymorphisms (SNPs) genotyped on 631 oat lines for association mapping of quantitative trait loci (QTL). Seedling reaction to crown rust in these lines was assessed as infection type (IT) with each of 10 crown rust isolates. Adult plant reaction was assessed in the field in a total of 10 location–years as percentage severity (SV) and as infection reaction (IR) in a 0‐to‐1 scale. Overall, 29 SNPs on 12 linkage groups were predictive of crown rust reaction in at least one experiment at a genome‐wide level of statistical significance. The QTL identified here include those in regions previously shown to be linked with seedling resistance genes Pc48, Pc58a, Pc68, Pc71, Pc91, and PcKM and also with adult‐plant resistance and adaptation‐related QTL. In addition, QTL on linkage groups Mrg03, Mrg08, and Mrg23 were identified in regions not previously associated with crown rust resistance. Evaluation of marker genotypes in a set of crown rust differential lines supported Pc91 as the identity of QPc.CORE.18.3 . The SNPs with rare alleles associated with lower disease scores may be suitable for use in marker‐assisted selection of oat lines for crown rust resistance.